2018
DOI: 10.1024/0301-1526/a000720
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of outcome quality in peripheral arterial disease revascularisations – a Delphi expert consensus

Abstract: This Delphi approach of vascular experts identified three indicators as highly relevant and clinically practicable to be recommended as indicators of outcome quality in invasive PAD treatment. Among others, these consented items may help in harmonising future studies and quality benchmarking increasing their comparability, validity, and efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Several previous studies looked at the effect of the use of quality indicators in various areas of care. 6,7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] A recent study compared SINAS quality indicators for ambulatory surgery with international-used indicators. 10 The authors concluded that, although SINAS is generally well adapted to current international practices, it would be useful/advisable to take into account two additional variables/factors, namely patient satisfaction and surgery cancellations during the scheduled day.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies looked at the effect of the use of quality indicators in various areas of care. 6,7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] A recent study compared SINAS quality indicators for ambulatory surgery with international-used indicators. 10 The authors concluded that, although SINAS is generally well adapted to current international practices, it would be useful/advisable to take into account two additional variables/factors, namely patient satisfaction and surgery cancellations during the scheduled day.…”
Section: Discussionmentioning
confidence: 99%
“…A normal ABI ranges between 0.9 and 1.3, and an ABI of <0.9 indicates LE-PAD, with lower values indicating more severe obstruction [ 14 ]. The Rutherford classification is a system used to categorize the severity of LE-PAD by correlating clinical symptoms with the severity of LE-PAD, with higher categories indicating more severe obstruction and ischemia [ 15 ]. All predictor variables were derived from clinical data obtained during the patients' initial visit.…”
Section: Methodsmentioning
confidence: 99%
“…We performed a retrospective cohort study of patients undergoing PVI for PAD using prospectively collected data in the VQI registry. The VQI is an Agency for Healthcare Research and Quality‐listed Patient Safety Organization 16 that collects more than 120 patient and procedure characteristics that were predefined by both national and international consensus 17,18 on vascular procedures at over 500 participating centers in the United States and Canada 19 . We successfully linked 82% of PVI patients to fee‐for‐service Medicare claims to identify late outcomes.…”
Section: Methodsmentioning
confidence: 99%